"Teaching is learning": creating a meaningful English L2 writing class with service-learning. (2nd January 2019) - Wang, Hung-chun
ABSTRACT: Integrating service-learning into content courses is a growing pedagogical model expanding in higher education institutes in many countries. To examine the application of this approach in English L2 writing classes, this study embarked on a tutor–tutee mentoring project at a Taiwanese university. The participants in this study served as writing tutors to help non-English majors with their writing skills. They went through five phases to complete their individual services—selecting a tutee, exploring the tutee's difficulty in writing, designing a workshop for the tutee, implementing the workshop, and reflecting upon their service experience. Probing the tutors' responses to a project evaluation survey, this study showed that the tutors generally considered the project to be beneficial for enhancing their writing skills, writing confidence, knowledge about how to improve academic writing, and awareness of their own capabilities in helping others. However, this project was limited in several aspects, such as the amount of time demanded, the tutors' levels of teaching knowledge and skills, and some tutors' lack of confidence. Based on the results, this study concludes by proposing pedagogical recommendations to help English writing teachers fuse this project into their writing curricula more effectively.